2017
DOI: 10.1038/s41598-017-06406-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of 5-aminolevulinic acid against low inorganic phosphate in neuroblastoma SH-SY5Y cells

Abstract: PiT-1 (encoded by SLC20A1) and PiT-2 (encoded by SLC20A2) are type-III sodium-dependent phosphate cotransporters (NaPiTs). Recently, SLC20A2 mutations have been found in patients with idiopathic basal ganglia calcification (IBGC), and were predicted to bring about an inability to transport Pi from the extracellular environment. Here we investigated the effect of low Pi loading on the human neuroblastoma SH-SY5Y and the human glioblastoma A172 cell lines. The results show a different sensitivity to low Pi loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Subsequently, disrupted Pi homeostasis inside and outside cells is expected to occur in IBGC. In our previous study, we demonstrated that mitochondrial-related ROS were produced by the disruption of Pi homeostasis [59]. In the present study, we showed that 12AC3O reduced the signal of Mito SOX, which evaluates mitochondrial oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…Subsequently, disrupted Pi homeostasis inside and outside cells is expected to occur in IBGC. In our previous study, we demonstrated that mitochondrial-related ROS were produced by the disruption of Pi homeostasis [59]. In the present study, we showed that 12AC3O reduced the signal of Mito SOX, which evaluates mitochondrial oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…9,10 ALA reportedly exerts a broad range of cytoprotective effects against cisplatin-induced nephrotoxicity, rhabdomyolysis-induced acute kidney injury, hypoxia-induced cardiomyocyte injury, and low phosphorus loading-induced neurotoxicity through its antioxidant abilities. [10][11][12][13] Herein, we investigated the potential use of ALA as a novel radioprotective drug for normal rectal and bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…ALA is distributed ubiquitously in mammalian cells and is a precursor of tetrapyrole compounds such as heme, which is essential in aerobic energy metabolism and the electron transport system . ALA reportedly exerts a broad range of cytoprotective effects against cisplatin‐induced nephrotoxicity, rhabdomyolysis‐induced acute kidney injury, hypoxia‐induced cardiomyocyte injury, and low phosphorus loading‐induced neurotoxicity through its antioxidant abilities . Herein, we investigated the potential use of ALA as a novel radioprotective drug for normal rectal and bladder mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…However, mitochondrial dysfunction is also downstream of these signaling pathways. In addition, some ion homeostasis and cell metabolism–related proteins were also found to be downregulated in synaptosomes based on our proteomic analysis, such as those in the solute carrier family (SLC9A6, SLC20A2) and potassium voltage‐gated channel subfamily A2 (KCNA2), tubulin alpha 8 (TUBA8), and tubulin beta 2B (TUBB2), all of which are highly associated with mitochondria during cell metabolism or apoptosis (Table S3, Supporting Information) . Therefore, our results reveal that Ginseng can regulate the function of mitochondria and may be useful for the treatment of central nervous diseases.…”
Section: Discussionmentioning
confidence: 62%